Agreement at PF: An Argument from Partial Control. (March 2016) - Landau, Idan
Abstract: Controlled null subjects (PRO) are semantically bound variables that bear morphological features. In certain environments of partial control, the morphological ϕ‐features (specifically, [person]) and the semantic value of PRO diverge. A natural explanation of the fact that the [person] feature of PRO is uninterpreted is that it is assigned at Phonological Form (PF). Given that this feature participates in agreement relations, we conclude that agreement must be (optionally or exclusively) a PF phenomenon.